2016
DOI: 10.15252/embr.201541489
|View full text |Cite
|
Sign up to set email alerts
|

Resetting cancer stem cell regulatory nodes upon MYC inhibition

Abstract: MYC deregulation is common in human cancer and has a role in sustaining the aggressive cancer stem cell populations. MYC mediates a broad transcriptional response controlling normal biological programmes, but its activity is not clearly understood. We address MYC function in cancer stem cells through the inducible expression of Omomyc-a MYC-derived polypeptide interfering with MYC activity-taking as model the most lethal brain tumour, glioblastoma. Omomyc bridles the key cancer stemlike cell features and affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 72 publications
(167 reference statements)
3
51
0
Order By: Relevance
“…This result was consistent with a previous study which suggested that MYC correlated with cancer stem cell properties [56, 57]. Transcripts of MYC could not be exclusively attributed to Notch activation due to the dim expression of Notch3 in the suspended lymphoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with a previous study which suggested that MYC correlated with cancer stem cell properties [56, 57]. Transcripts of MYC could not be exclusively attributed to Notch activation due to the dim expression of Notch3 in the suspended lymphoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that MIAT is selectively upregulated in neuroendocrine prostate cancer and may interact with polycomb genes [16]. Myc inhibition could increase the expression of MIAT in glioblastoma cells [31]. Luan et al have found that MIAT promotes breast cancer progression and functions as a ceRNA to regulate DUSP7 expression by sponging miR-155-5p [24].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MYC in normal human cells may be ineffective or highly destructive, resulting in stagnation of proliferation, aging, or apoptosis. 110 MYC is usually deregulated in human cancers, plays an important role in maintaining the number of invasive CSCs, 111 and is also one of the most effective oncogenes for detecting the cell transformation phenotype in vitro and in vivo. Previous studies have shown that deletion of the tumor suppressor gene p53 and MYC synergizes to induce hepatocyte proliferation and tumorigenesis.…”
Section: Major Transcription Factors In Cscsmentioning
confidence: 99%